2008
DOI: 10.1007/s00586-008-0846-z
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar lordosis in osteoporosis and in osteoarthritis

Abstract: The curvature of the lumbar spine and the risk of developing either osteoporosis (OP) or osteoarthritis (OA) are influenced by many common factors. The aim of this study is to determine whether lumbar lordosis is different between patients with either disease and healthy persons. A crosssectional, blinded, controlled design was implemented. One hundred and twelve postmenopausal women were evaluated for bone mineral density as well as undergoing spinal radiography. Lordosis measurement was performed with Cobb's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The higher bone quantity and better mechanical quality could partly explain why femoral neck fractures were so rare in those people with OA [ 32 ]. However, Papadakis M et al [ 33 ] observed that the degree of lumbar lordosis was not associated with the presence of OA or OP. The reasons for the lack of difference may be due to, we believe, the size of sample, the criteria of subgroup, and the age of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The higher bone quantity and better mechanical quality could partly explain why femoral neck fractures were so rare in those people with OA [ 32 ]. However, Papadakis M et al [ 33 ] observed that the degree of lumbar lordosis was not associated with the presence of OA or OP. The reasons for the lack of difference may be due to, we believe, the size of sample, the criteria of subgroup, and the age of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lordosis, another condition that may complicate interpretation of spine densitometry results, may be even more important because osteoporosis and spinal deformities (lordosis and scoliosis) are interrelated. A higher prevalence of spinal deformities has been demonstrated in osteoporosis patients than in individuals without osteoporosis (10,11). In patients who have varying degrees of lordosis, the lumbar vertebrae do not lie horizontally on the scanning table (i.e., each is not equally distant from the xray source and detector), even after a positioner is placed beneath the legs.…”
mentioning
confidence: 99%